Comparative Analysis of Learning With Jigsaw and Think Pair Share (TPS) on Mathematical Problem Solving Abilities on The Properties of Exponents in Grade X - Jois Febri Manik; Hardi Tambunan; Samuel Juliardi Sinaga (Jurnal Pendidikan, Sains Sosial, dan Agama, 2021)
This study aims to analyze the comparison of cooperative learning models, Jigsaw and Think Pair Share (TPS), on students’ mathematical problem-solving abilities in the topic of exponent properties among tenth-grade students at SMK Free Methodist Medan in the 2025/2026 academic year. The research method employed was a quasi-experimental design with a pretest-posttest group design. The population consisted of all tenth-grade students at SMK Free Methodist Medan, while the sample included two classes: class X RPL taught using the Jigsaw model and class X TKJ taught using the TPS model. The research instrument was an essay test developed based on mathematical problem-solving indicators, and the data were analyzed using an independent samples t-test.The results of the study indicate that: (1) there is a significant difference in mathematical problem-solving abilities between students taught with the Jigsaw and TPS models (sig. 0.023 < 0.05), and (2) the Jigsaw learning model is more effective than the TPS model in improving students’ mathematical problem-solving abilities (sig. 0.011 < 0.05). Therefore, the Jigsaw learning model is recommended as a superior alternative cooperative learning strategy to enhance students’ mathematical problem-solving skills in the topic of exponents at the vocational high school level